FILSAFAT ILMU SEBAGAI BASIS INOVASI KURIKULUM MANAJEMEN PENDIDIKAN ISLAM - Elviani Sartika; Suminto; Yatin Mulyono (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Philosophy of science plays a fundamental role in constructing a systematic, rational, and critical scientific framework in curriculum development. In the context of Islamic educational management, curriculum innovation requires not only technical approaches but also a strong philosophical foundation to respond to contemporary challenges without losing Islamic values. This study aims to analyze the role of philosophy of science as a basis for curriculum innovation in Islamic educational management. This research employs a qualitative approach using a library research method through the analysis of books, academic journals, and other relevant sources. The findings indicate that philosophy of science contributes to three main aspects: the ontological aspect related to the nature of knowledge and the goals of Islamic education, the epistemological aspect related to methods and approaches in curriculum development, and the axiological aspect related to values and orientation of the curriculum. The integration of these aspects produces a curriculum innovation model that is adaptive to contemporary developments while remaining grounded in Islamic values. This study contributes conceptually to the development of philosophy-based curriculum innovation in Islamic educational management.